Perception of Management Scholars for Course Specialization Decision in Kathmandu Valley - Lamichhane, Basu Dev; Lama, Padam Bahadur; Pandey, Prerna; Lamichhane, Saujan; PC, Sweta (Journal of Business and Management, 2025)
Background: The University offers plenty of courses to cultivate academic careers and enhance professionalism among the scholars. Similarly, evolution of modern market with competitive scenario requires competent resources to mitigate diverse challenges. Thus, the adoption of courses by college scholars plays a vital role for driving the future industry and market. Moreover, the course selection decision of college students relies on several dimensions and factors. Objectives: The main aim of this study is to examine the determinants of students’ specialization choices. This study adopted independent variables future prospects (FP), family factors (FF), and market trends (MT), and dependent variables as specialization decisions (SD). Methods: The research design embraced in the study consists of descriptive, relational, and causal research designs. To assess the relationship of learners’ specialization choices, a survey with a structured questionnaire was used to collect the information. A structural questionnaire was distributed among the respondents to give the responses freely. Thus, the study utilized 102 respondents for analysis. This research utilized frequency, mean, median, mode, correlation, and regression analysis for the statistical segment. Results: The findings of the study revealed a positive and significant influence of prospects on course specialization (β = 0.336, p <0.05). Similarly, a positive and significant effect of family factors was found on course decisions (β = 0.245, p <0.05). Finally, results depicted a positive and significant influence of market opportunity trend on course specialization decision (β = 0.337, p <0.05). Thus, the findings of the study revealed that the future prospect, market trend, and family factors positively link with course specialization decision. Conclusion: The findings of the study depicted that the course selection decisions of college students are influenced in favorable ways by the future prospect of the course, market trends, and family factors advocating the significant role of family consultation, requirement of market and future prospects. JEL Classification: A22, I20, M10